COVID-19 INFECTION IN A CANDIDATE FOR AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANTATION: A CASE REPORT: A case report - Lira, Mateus Lavor; Lima, Yara Ceres e Silva Ferreira; de Figueiredo Júnior, Isaias Lima; Oliveira Neto, Osvaldo Pimentel; Duarte, Isabella Araujo; Duarte, Beatrice Araujo; Duarte, Fernando Barroso (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2020)
The pandemic for the new coronavirus SARS-CoV-2 has been the causeof enormous challenges for the entire health system, especially in programs who dealwith Hematopoietic Stem Cell Transplantation (TCTH), since sequelae related to COVID-19 can be a hindrance to a possible HSCT. In case report, VBF, 61 years old, diagnosis of classic lymphocyte-rich Hodgkin'slymphoma in 2018 with initial treatment with ABVD, due to the return of the disease, an ICE regimen was started, but with disease progression after 5 cycles. Then, an IGEV scheme was started with a schedule of autologous hematopoietic cell transplantation, which took place in the third cycle in May / 2020. However, at the end of May / 2020, he was admitted to the emergency department with confirmation of SARS-Cov-2 infection by means of PCR of the nasal and oropharyngeal swab. He evolved during hospitalization with hypoxemic respiratory failure, mechanical ventilation and signs of secondary pulmonary infection, using multiple antimicrobial regimens, showing improvement and finally being extubated. However, he presented important pulmonary sequelae, with chest CT showing extensive cavitation in the left upper lobe and reticular opacities, with distortion of the pulmonary architecture. He was reassessed as to the possibility of autologous hematopoietic cell transplantation, but this was contraindicated due to pulmonary sequelae. In the case reported, the patient complied with the formal indication for HSCT, which would be refractoriness or relapse in a second remission in patients up to 70 years old with sensitivity to rescue schemes. However, due to pulmonary sequelae acquired after COVID-19, HSCT was contraindicated. This case leads us to the conclusion that the pandemic by the SARS-CoV-2 coronavirus can directly affect HSCT services and that in addition to preventing infection in this group of patients, they should be reevaluated after the recovery of COVID-19 for evaluation of structural and functional respiratory sequelae.